Review of Equity Crowdfunding Practices through Santara.id in the Perspective of Islamic Economic Law - Octaviani, Rahma; Pamesti, Pas Ingrid; Heradhyaksa, Bagas (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This article aims to find out the mechanism of equity crowdfunding through the santara platform from Islamic economic law. This article uses a qualitative method using library data. This article finds that santara.id is an intermediary between investors and issuers in developing a business. The scheme is similar to the muá¸Ärabah contract, the investor is identical to á¹£Äá¸¥ib al-mÄl, and the issuer is identical to the muá¸Ärib. However, this activity cannot be considered as muá¸Ärabah cooperation because there has been no concrete agreement regarding the muá¸Ärabah agreement. This article provides suggestions so that santara.id can further develop the platform's promotion in the community. It is because santara.id can provide investment services for the middle class, both as investors and issuers.